Mongolian sound worlds - Post, Jennifer C.; Yoon, Sunmin; D'Evelyn, Charlotte (University of Illinois Press, 2022)
"Music cultures today in rural and urban Mongolia and Inner Mongolia emerge from centuries-old pastoralist practices that were reshaped by political movements in the twentieth century. Mongolian Sound Worlds investigates the unique sonic elements, fluid genres, social and spatial performativity, and sounding objects behind new forms of Mongolian music--forms that reflect the nation's past while looking towards its globalized future. Drawing on fieldwork in locations across the Inner Asian region, the contributors report on Mongolia's genres and musical landscapes; instruments like the morin khuur, tovshuur, and Kazakh dombyra; combined fusion band culture; and urban popular music. Their broad range of concerns include nomadic herders' music and instrument building, ethnic boundaries, heritage-making, ideological influences, nationalism, and global circulation. A merger of expert scholarship and eyewitness experience, Mongolian Sound Worlds illuminates a diverse and ever-changing musical culture"--